On the Hosoya Index of Some Families of Graph - Fateme Movahedi; Mohammad Hadi Akhbari; Hailiza Kamarulhaili (Mathematics Interdisciplinary Research, 2021)
‎We obtain the exact relations of the Hosoya index that is defined as the sum of the number of all the matching sets‎, ‎on some classes of cycle-related graphs‎. ‎Moreover‎, ‎this index of three graph families‎, ‎namely‎, ‎chain triangular cactus‎, ‎Dutch windmill graph‎, ‎and Barbell graph is determined‎.